Degradation Effect of Moisture on Mechanical Properties of Kevlar/PVB Composites with TiO2 Nanoparticles - Vera Obradović; Petr Sejkot; Adam Zabloudil; Klára V. Machalická; Miroslav Vokáč (Buildings, 2024)
Kevlar fibers are widely used for industrial and military purposes due to their remarkable mechanical properties, such as their high tenacity and high strength-to-weight ratio. In this study, two-layered Kevlar composite specimens were impregnated with 10 wt.% poly (vinyl butyral)/ethanol solution which contained TiO2 nanoparticles as reinforcement. The concentrations of the nanoparticles were 1 wt.% or 2 wt.% with respect to the poly (vinyl butyral), PVB. The single-axial tensile test and three-point bending test of the Kevlar/PVB composites have been performed according to the ASTM D 3039 and ASTM D 790-03 standards, respectively. The tensile and bending properties of the dry and wet Kevlar/PVB composite specimens after a 56-day immersion are examined in this work. Upon the addition of the 2 wt.% TiO2 nanoparticles, the tensile strength and modulus of the dry specimens without reinforcement were increased by 39.8% and 24.3%, respectively. All the submerged specimens’ tensile and flexural property values were lower than those of the dry specimens. After comparing the wet composite specimens to their dry counterparts, the percentage decrease in tensile strength was approximately 20%. The wet Kevlar/PVB specimens with no TiO2 reinforcement showed the greatest reduction in bending strength, 61.4% less than for the dry Kevlar/PVB specimens, due to the degradation of the PVB matrix. In addition, a numerical simulation of the three-point bending test was carried out in Abaqus.